Ecological study of gastropod on seagrass ecosystem in small island sea North Maluku Indonesia - Sunarti Sunarti; Yuyun Abubakar; Salim Abubakar; Riyadi Subur; Rina Rina; Nebuchadnezzar Akbar; Raut Nugrahening Widhi; Mesrawaty Sabar; Raut Wahyuning Paluphi; Disnawati Disnawati (Depik, 2025)
The seagrass ecosystem is a habitat and food source for fish and other aquatic biota. One of the biota commonly found in seagrass beds is gastropods . This aim research was carried of identifying the composition of gastropod species, assessing ecological indices which include species density, species diversity, species dominance, species evenness, distribution patterns of gastropods and their use in the seagrass ecosystem on Maitara Island. Gastropod sampling was carried out at low tide. The gastropod samples determined based on morphological characteristics such as shell shape, shell color, shell mouth opening and spiral circle. Based on the research results, the composition of gastropod species found in the seagrass ecosystem is 32 species. The density of gastropod species was highest in the seagrass ecosystem on Maitara Island, at each different station. The highest density of gastropod species was Morula uva and Strombus luhuanus, while the lowest density was Trhocus maculatus, Littorina scabra and Nassarius sp. The diversity of gastropod species at all stations is classified as moderate. For the dominance index at all stations, there is no dominant species in the category. The evenness of species at station 1 and 4 is classified as more evenly distributed, while at stations 2 dan 3 it is classified as very evenly distributed. The overall distribution pattern of gastropods is classified as clustered and random. Totals 32 species of gastropods, 10 of them are used by the people of Maitara Island as food for consumption.Keywords:benthicconditionimpacttropicalsurvival